Autophagy Is a Defense Mechanism Inhibiting Invasion and Inflammation During High-Virulent Haemophilus parasuis Infection in PK-15 Cells - Yue, Chaoxiong; Li, Jinquan; Jin, Hui; Hua, Kexin; Zhou, Wei; Wang, Yueyi; Cheng, Guirong; Liu, Dan; Xu, Lang; Chen, Yushan; Zeng, Yan (Frontiers in Cellular and Infection Microbiology, 2019)
Bacterial infections activate autophagy and autophagy restricts pathogens such as Haemophilus parasuis through specific mechanisms. Autophagy is associated with the pathogenesis of H. parasuis. However, the mechanisms are not clarified. Here, we monitored autophagy process using confocal microscopy, western blot, and transmission electron microscopy and found that H. parasuis SH0165 (high-virulent strain) but not HN0001 (non-virulent strain) infection enhanced autophagy flux. The AMPK/mTOR autophagy pathway was required for autophagy initiation and ATG5, Beclin-1, ATG7 and ATG16L1 emerged as important components in generation of the autophagosome during H. parasuis infection. Moreover, autophagy induced by H. parasuis SH0165 turned to fight against invaded bacteria and inhibit inflammation. Then we further demonstrated that autophagy blocked the production of the cytokines IL-8, CCL4 and CCL5 induced by SH0165 infection through inhibition of NF-κB, p38 and JNK MAPK signaling pathway. Therefore, our findings suggest that autophagy may act as a cellular defense mechanism in response to H. parasuis and provide a new way that autophagy protects the host against H. parasuis infection.